Organisasiestrukture van landbou-ontwikkelingsinstellings - J. Kroon; H. J.P. Steyn (South African Journal of Business Management, 1993)
Organization structures of agricultural development Institutions. Agriculture plays an important role in the economic activities of the developing regions of Southern Africa. The public sector has an important role to play in promoting agricultural development. This role can be fulfilled by government departments. These inititutions are, however, often restricted in this function. As a result of this, all the independent states and self-governing territories in Southern Africa have created independent institutions to undertake agricultural development. In this article, attention is firstly given to a short description of agricultural development institutions and following that, the approach in organizational design is given. An analysis of the environment in which agricultural development institutions operate is given to serve as basis for proposing a development strategy for these institutions. Based on this proposed strategy, the functions to be performed by agricultural development institutions are formulated, and an organizational structure for agricultural development institutions, is proposed.Landbou speel 'n belangrike rol in die ontwikkelende gebiede van Suider Afrika. Die openbare sektor het 'n groot verantwoordelikheid ten opsigte van die bevordering van landbou-ontwikkeling. Hierdie rol kan deur staatsdepartemente vervul word. Weens verskeie organisatoriese beperkings van sulke instellings het al die onafhanklike state en selfregerende gebiede in Suider Afrika onafhanklike korporatiewe instellings vir landbou-ontwikkeling geskep. In hierdie artikel word landbou-ontwikkelingsinstellings beskryf. Daarna volg 'n bespreking van 'n benadering tot organisasie-ontwerp. 'n Ontleding van die omgewing waarin sodanige instellings funksioneer, dien as basis vir die formulering van 'n toepaslike ontwikkelingstrategie. Met die strategie as basis word die funksies van landbou-ontwikkelingsinstellings bepaal, en 'n organisasiestruktuur voorgestel.
Keywords: 650